Return Spillovers among Emerging Asian Stock Markets along the Belt and Road Initiative: Evidence from 2005-2023: https://doi.org/10.55966/assaj.2025.4.1.0101 - Muhammad Asif Ali; Dr. Said Shah; Dr. Faisal Khan* (`, 2025)
This study investigated the magnitude and directions of return spillovers among 10 emerging Asian equity markets along Belt and Road Initiative from 2005–2023. We measured total, directional, and net Spillovers across these markets by applying Diebold and Yilmaz (2012) spillover index framework on daily stock index returns. The results show significant return interdependence, with substantial time varying fluctuations, particularly during major world crises like Global Financial Crises of 2008 and COVID-19 pandemic. The findings demonstrate that Indian BSE and Malaysian KLCI are net transmitters of return spillovers as they transmit more shock than they receive. Thailand’s SET, Sri Lanka’s CSE and Pakistan’s KSE largely function as net recipients of return shocks. This study is helpful in understanding regional financial integration among emerging markets along Chinese Belt and Road initiative. It also provides valuable insights in order to facilitate efficient portfolio diversification strategies and policy formulation in emerging Asian countries. Keywords: Belt and Road Initiative, Covid-19 Pandemic, Global Financial Crises, Return Spillovers, Stock Markets.